Study of Translation Strategies for Culturally Loaded Terms in Spanish: Based on Grounded Theory (Sinología hispánica. China Studies Review, 2025)
Culturally loaded words that frequently appear in people's daily lives carry the historical and cultural characteristics of a country, playing a crucial role in intercultural communication. Based on materials from major language textbooks from China and Spain, and using a sample of 30 translators, this study applies grounded theory to investigate culturally loaded words in daily communication texts in Chinese and Spanish, as well as the translation strategies employed. Through translation tests with the 30 translators and two rounds of semi-structured interviews, original interview data were collected and organized, and coding was carried out at three levels. A total of 32 initial concepts were extracted, and through comparison and induction, 12 fundamental categories were formulated, which eventually led to the identification of 5 core concepts. The study reveals that when translating culturally loaded terms, translators tend to preserve the cultural connotation of the term in 90% of cases when source language factors are predominant, whereas they prioritize the reader's understanding of the text in 10% of cases when target language factors are more influential. Among the seven translation strategies identified, “intratextual explanation” and “analogy” are the most frequently used.